2019
DOI: 10.3390/medicina55070328
|View full text |Cite
|
Sign up to set email alerts
|

Urotensin 2 and Oxidative Stress Levels in Maternal Serum in Pregnancies Complicated by Intrauterine Growth Restriction

Abstract: Background and objectives: In this study, the aim was to investigate Urotensin 2 (U-II) levels and oxidant/antioxidant system parameters in pregnancies with intrauterine growth restriction (IUGR). Materials and Methods: A total of 36 healthy, pregnant women who had not been diagnosed with IUGR and 36 pregnant women who had been diagnosed with IUGR at the Obstetrics and Gynecology Outpatient Clinic at Gaziantep University Hospital were enrolled in this study. The serum total antioxidant status (TAS), total oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…In our study, only patients with diagnosed IUGR without hypertension were included and no oxidative stress in plasma was noted. Similar results were obtained by Celik et al, who compared the oxidative stress index and the total antioxidant and total oxidant status in uncomplicated pregnancy and IUGR [ 53 ]. Others observed severe OS in IUGR patients.…”
Section: Discussionsupporting
confidence: 86%
“…In our study, only patients with diagnosed IUGR without hypertension were included and no oxidative stress in plasma was noted. Similar results were obtained by Celik et al, who compared the oxidative stress index and the total antioxidant and total oxidant status in uncomplicated pregnancy and IUGR [ 53 ]. Others observed severe OS in IUGR patients.…”
Section: Discussionsupporting
confidence: 86%
“…Dynamic thioldisulfide balance has been described as a relatively new marker of oxidative stress, and it is stated in the literature that it contributes to antioxidant protection, detoxification, and apoptosis (21) . In a study conducted by Celik et al,They reported that they did not find any statistically significant difference in terms of total thiol, nativ tiyol, disülfid,nativ tiyol/total tiyol,disülfid /nativ tiyol ve disülfid /total tiyol values in the comparison between the group with IUGR and the healthy pregnant group (6) . This part of the research was consistent with our findings.Oxidative stress, inflammation,and endothelial cell dysfunction play crucial roles in the pathogenesis of atherosclerosis (10) .…”
Section: Discussionmentioning
confidence: 93%
“…If ROS production increase or antioxidant mechanisms decline,a condition occurs by biological system which defined as oxidative stress.Oxidative stress is an imbalance between oxidants and antioxidants on the side of oxidants (5) . Oxidative stress is considered to play a vital role in the improvement of placental inadequacy,that is one of the main reason of IUGR pathogenesis (6) . Oxidized low density lipoprotein (OxLDL) promotes to atherosclerotic plaque formation and progression by various mechanisms, including macrophage foam cell formation,induction of endothelial cell dysfunction and activation, and smooth muscle cell proliferation and migration (7) .…”
Section: Introductionmentioning
confidence: 99%
“…IUGR animals are more susceptible to OS, an effect that is probably associated with the dysregulation between prooxidants and antioxidants. Besides, excess OS affects cell homeostasis and could predispose to cell injuries (Biri et al, 2007;Celik et al, 2019). Such dysregulation leads to cell damage, which may even result in cell death as well as irreversible oxidative damage if it remains to be out of control, nally negatively affecting organism survival and function (Yin et al, 2013b).…”
Section: Discussionmentioning
confidence: 99%